2014
DOI: 10.1017/s0022215114002515
|View full text |Cite
|
Sign up to set email alerts
|

Does gestational diabetes result in cochlear damage?

Abstract: An investigation into cochlear damage in gestational diabetic patients showed significant high-frequency hearing loss. Further studies are needed to validate these findings in different ethnic groups and geographical populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…Although this study did not ind association between hearing impairment and gestational diabetes, Selcuk, et al [4], found higher frequency of hearing loss in patients with gestational diabetes.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Although this study did not ind association between hearing impairment and gestational diabetes, Selcuk, et al [4], found higher frequency of hearing loss in patients with gestational diabetes.…”
Section: Discussioncontrasting
confidence: 73%
“…Recent studies report that the presence of maternal comorbidities may interfere in the occurrence of hearing loss in postpartum women [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…One small case-control study of 27 patients with gestational diabetes and 31 nondiabetic pregnant women found significantly elevated high-frequency auditory thresholds (8,000-14,000 Hz) among women with gestational diabetes. 45 Additional work is needed in this area to better understand the possible relationship between gestational diabetes and auditory damage.…”
Section: Gestational Diabetes and Hearing Lossmentioning
confidence: 99%
“…9 Gestational diabetes mellitus can cause complications in pregnancy similar to those seen in pre-existing diabetes mellitus. 3,14 From the aforesaid account it would be reasonable to assume that cochlear dysfunction might be an outcome of gestational diabetes as the inner ear is sensitive to altered glucose metabolism in GDM. 14,15 Etiopathogenesis of this hearing loss due to DM is attributed physiologically to neuropathy and angiopathy or a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…3,14 From the aforesaid account it would be reasonable to assume that cochlear dysfunction might be an outcome of gestational diabetes as the inner ear is sensitive to altered glucose metabolism in GDM. 14,15 Etiopathogenesis of this hearing loss due to DM is attributed physiologically to neuropathy and angiopathy or a combination of both. 3,[14][15][16][17][18] The cochlea may also be a The impact of GDM on hearing loss has not been adequately explored, in spite of the involvement of the sense of hearing.…”
Section: Introductionmentioning
confidence: 99%